THE RELATIONSHIP BETWEEN Fe ADEQUACY, DIETARY PATTERN AND MIDDLE UPPER ARM CIRCUMFERENCE (MUAC) LEVEL WITH ANEMIA IN PREGNANCY AT PUSKESMAS SIMPANG KAWAT JAMBI CITY - Ruwayda Ruwayda; Nurmisih Nurmisih (Poltekkes Kemenkes Jambi, 2019)
Background: The incidence rate of anemia in Indonesia shows a high value. Anemia is a decrease in the quantity or quality of red blood cells in the circulation. Anemia that often occurs in pregnancy is iron deficiency anemia. Deficiency of nutritional status could be the predispotitional factor of anemia in pregnancy in Indonesia. One of the indicator of nutritional status is the measurement of Middle Upper Arm Circumference MUAC) level. This research was aimed to determine the the relationship between Fe adequacy, dietary pattern and Middle Upper Arm Circumference (MUAC) level with anemia in pregnancy at Puskesmas Simpang Kawat Jambi city. Methods: This research was a descriptive research with crosssectional design. A total of 97 respondents were recruited from a population of 526 using quota sampling. The respondent was pregnant women who visited the maternal and child health room of Puskesmas Simpang Kawat Jambi City. Results: The results showed that 72 respondents had anemia (74,2%). There is a correlation of consumption consumption of fe tablet with anemia of pregnant mother (p = 0,006). But there was no dietary association (p = 0,279) and size of upper arm circumference with anemia of pregnant mother (p = 0,178). Conclusion: There is a correlation of consumption consumption of Fe tablet with anemia of pregnant mother . But there was no dietary association and size of upper arm circumference with anemia of pregnant mother.